2021
DOI: 10.3389/fmolb.2021.792319
|View full text |Cite
|
Sign up to set email alerts
|

Urine Organic Acids as Metabolic Indicators for Global Developmental Delay/Intellectual Disability in Chinese Children

Abstract: Objective: The purpose of this study was to search for differential metabolites in urine organic acids, and to characterize metabolic features that can be used to identify metabolites for exploration of global developmental delay (GDD)/intellectual disability (ID) etiology and pathogenesis.Methods: We screened positive test results that could explain GDD/ID from 1,253 cases, and the major differential metabolites in 132 urine organic acids from the 1,230 cases with negative results (863 GDD cases, 367 ID cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Specifically, in those with DD, we found involvement of ATP and other energy metabolites. Previous studies show elevations in the TCA and energy pathway metabolites in both urine [ 21 ] and plasma [ 13 , 14 ]. Studies examining the characteristics of those with ASD and mitochondrial disorder demonstrate a high incidence of DD, particularly motor delay [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in those with DD, we found involvement of ATP and other energy metabolites. Previous studies show elevations in the TCA and energy pathway metabolites in both urine [ 21 ] and plasma [ 13 , 14 ]. Studies examining the characteristics of those with ASD and mitochondrial disorder demonstrate a high incidence of DD, particularly motor delay [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with DD have been shown to have increased glycolic and 3-hydroxyisobutyric acid and decreased palmitic acid [ 21 ] in urine and elevated acetate, glutamate, lactate and tricarboxylic acid (TCA) cycle metabolites in plasma [ 13 ]. Interestingly, one study that included DD and ASD participants demonstrated that cognitive function, adaptive skills, and aberrant behavior were related to some of these same metabolites [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The repeated association of energy metabolism with many aspects of ASD is not surprising given the high rate of mitochondrial dysfunction associated with ASD [ 10 , 11 ]. Furthermore, the link to neurodevelopment and language is not surprising as previous studies have linked developmental delays to abnormal CAC and energy pathway biomarkers in urine [ 54 ], plasma [ 55 , 56 ], and CSF [ 34 ]. Children with ASD and mitochondrial disease appear to have two developmental profiles, those with developmental delays, including motor delay, and those that manifest NDR [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is imperative to consider metabolic disorders such as congenital hypothyroidism, phenylketonuria, and methylmalonic acidemia as potential underlying causes of GDD/ID. 14,15) In addition to central nervous system malformations, brain injury leading to neurodevelopmental disabilities can stem from pre-and postnatal complications such as asphyxia, congenital and acquired infections, kernicterus, and head trauma. 16,17) Uncontrolled maternal medical conditions and environmental exposure during pregnancy can precipitate GDD/ID.…”
Section: Risk Factors and Etiologiesmentioning
confidence: 99%